INTUISI SISWA KELAS VII SMP NEGERI 1 NGANJUK DALAM PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Erdyna Dwi Etika; Imam Sujadi; Sri Subanti (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aims of this research were to describe: (1) the category of intuition of seventh grade student of SMPN 1 Nganjuk with type of climber, camper, and quitter in solving mathematics problems. (2) the type of intuition of seventh grade student of SMPN 1 Nganjuk with type of climber, camper, and quitter in solving mathematics problems. The type of this research was a case study research. The prosedure of selecting the subject used purposive snowball sampling. Data was collected by using think aloud method. To determine the validity of data was undertaken with time-triangulation. The results showed as follows: (1) The category of intuition on the students of SMP N 1 Nganjuk : (a) students with climbers type, students used category affirmatory intuition in understanding the problem; students used affirmatory intuition in devising a plan; students used anticipatory intuition in carrying out the plan; students used affirmatory intuition in looking back the answer. (b) Students with campers types, students used affirmatory intuition in understanding the problem; students used antisipatori intuition in devising a plan; students didn’t use intuition in carrying out the plan; students didn’t use intuition in looking back the answer. (c) Students with quitters types, students didn’t use intuition in understanding the problem; students used affirmatory intuition in devising a plan; students used anticipatory intuition in carrying out the plan; students didn’t use intuition in looking back the answer. (2) Type of intuition on students of SMP N 1 Nganjuk: (a) Students with climber types, students used intuition based on the senses in understanding the problem; students used intuition based on the senses in devising a plan; students use intuition based on the senses in carrying out the plan; students used intuition based on the senses in looking back the answer. (b) Students with campers types, students used intuition based on the senses in understanding the problem; students used intuition based on real mathematical thinking in devising a plan; students didn’t use intuition in carrying out the plan; students didn’t use intuition in looking back the answer. (c) Students with quitters types, students didn’t use intuition in understanding the problem; students used intuition based on the senses in devising a plan; students used intuition based on the sense in carrying out the plan; students didn’t use intuition in looking back the answer.Keywords: Intuition, Category of intuition, Type of intuition, Adversity Quotient (AQ)